Impact of pre‐existing mental health disorders on the receipt of guideline recommended cancer treatments: A systematic review. Issue 3 (10th January 2023) - Wang, Yueh‐Hsin; Aggarwal, Ajay; Stewart, Robert; Davies, Elizabeth A.
Abstract: Objective: Disparities in cancer outcomes for individuals with pre‐existing mental health disorders have already been identified, particularly for cancer screening and mortality. We aimed to systematically review the influence on the time from cancer diagnosis to cancer treatment, treatment adherence, and differences in receipt of guideline recommended cancer treatment. Methods: We included international studies published in English from 1 January 1995 to 23 May 2022 by searching MEDLINE, Embase, and APA PsycInfo. Results: This review identified 29 studies with 27 being published in the past decade. Most studies focused on breast, non‐small cell lung and colorectal cancer and were of high or medium quality as assessed by the Newcastle Ottawa Scale. All studies were from high‐income countries, and mostly included patients enrolled in national health insurance systems. Five assessed the impact on treatment delay or adherence, and 25 focused on the receipt of guideline recommended treatment. 20/25 studies demonstrated evidence that patients with pre‐existing mental health disorders were less likely to receive guideline recommended therapies such as surgery or radiotherapy. In addition, there was a greater likelihood of receiving less intensive or modified treatment including systemic therapy. Conclusions: Across different cancer types and treatment modalities there is evidence of a clear disparity in the receipt of guideline recommended cancer treatment for patients with pre‐existing mental health disorders. The effect of pre‐existing mental health disorders on treatment delay or adherence is under‐researched. Future research needs to include low‐ and middle‐income countries as well as qualitative investigations to understand the reasons for disparities in cancer treatment.